2022
DOI: 10.1021/acsami.2c17625
|View full text |Cite
|
Sign up to set email alerts
|

Tunable 0D/2D/2D Nanocomposite Based on Green Zn-Doped CuInS2 Quantum Dots and MoS2/rGO as Photoelectrodes for Solar Hydrogen Production

Abstract: Charge separation, transmission, and light absorption properties are critical to determining the performance of photoelectrochemical (PEC) devices. An important strategy to control such properties is based on using heterostructured materials. Herein, a tunable zero-dimensional (0D)/two-dimensional (2D) heterostructure is designed based on quantum dots (QDs) and 2D nanosheets (NSs). Specifically, eco-friendly Zn-doped CuInS2 QDs prepared by hot injection were anchored on hierarchical (2D/2D) MoS2/rGO (MG) NSs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The PEC performances of Cubased QD-sensitized photoanodes are summarized in Table 1. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][83][84][85][86][87][88]…”
Section: Meanwhile Tong Et Al Synthesized Pyramidal-shapedmentioning
confidence: 99%
“…The PEC performances of Cubased QD-sensitized photoanodes are summarized in Table 1. [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][83][84][85][86][87][88]…”
Section: Meanwhile Tong Et Al Synthesized Pyramidal-shapedmentioning
confidence: 99%
“…33 Electrochemical sensor performance was affected considerably by experimental parameters (pH value and accumulation time), so these parameters have been investigated and optimized. 34 The DPV curves of 50 μM CAP at MoS 2 -3/SPE with different pH values (3)(4)(5)(6)(7)(8)(9)(10)(11) were shown in Fig. S1.…”
Section: R Nhoh R No 2e 2hmentioning
confidence: 99%
“…In fact, both theoretical and experimental evidence have demonstrated that the addition of MoS 2 could greatly increase the electrochemical performance owing to these characteristics. [6][7][8][9][10] Indeed, Dinh et al 11 chose 2D-MoS 2 nanomaterial as an essential factor for the development of working electrodes in electrochemical sensor applications toward the sensitive determination of chloramphenicol (CAP). As expected, the MoS 2 -modified electrode offered a wider concentration linear range (0.5-50 μM) and a smaller LOD value (61 nM).…”
mentioning
confidence: 99%
“…Apart from these cases, other systems like CuInS 2 –C, 207–209 CuInS 2 –Ti 3 C 2 210 and CuInS 2 –MoS x 211–213 have also been reported in recent years, based on either self-assembly of two-dimensional materials or e-beam evaporation-sulfurization. We would not emphasize too much on these systems because intrinsically they are not epitaxially grown.…”
Section: Nanocrystal Hybridizationmentioning
confidence: 99%